Analisis Pengukuran Kinerja Keuangan Studi pada LAZISMU Sulawesi Selatan Tahun 2019-2021 Ditinjau dari Rasio Efisiensi - Rahmadani, Devi; Yunus, Ayu Ruqayyah; Katman, Muhammad Nasri (Asian Journal of Islamic Studies and Da'wah, 2024)
The aim of this research is to determine the financial performance of LAZISMU South Sulawesi in 2019-2021 in terms of efficiency ratios. The type of research data used is secondary data with a descriptive qualitative approach. The data source in this research wash optained from financial reports provided directly by LAZISMU South Sulawesi in the form of Excel files. The sample in this research is financial performance data for the 2019 to 2021 period at LAZISMU South Sulawesi. Data analysis uses the OPZ ratio published by PUSKAS BASNAS 2019, namely analysis of efficiency ratio measurements. The result of this calculation show that in the first calculation, the efficiency ratio is the calculation of the collection cost ratio in 2019. it is in the efficient category, and in 2020 it is in the quite efficient category, finally in 2021 it is in the efficient category, in 2020 it is in the quite efficient category, finally in 2021 it is in the efficient category. Second, the calculation of operational costs for total amil right in 2019 shows quite efficient results, whereas in 2019-2020 it shows inefficient results. Furthermore, the calculation of operational costs towards total collections in 2019 and 2021 shows inefficient results, while in 2020 it was categorized as quite efficient. Third, based on the efficiency ratio from calculating the HR/Human Resources cost ratio, in 2020-2021, results show efficient results.